2010
DOI: 10.1111/j.1468-2958.2010.01393.x
|View full text |Cite
|
Sign up to set email alerts
|

The Disclosure-Intimacy Link in Computer-Mediated Communication: An Attributional Extension of the Hyperpersonal Model

Abstract: The present research investigated whether the attribution process through which people explain self-disclosures differs in text-based computer-mediated interactions versus face to face, and whether differences in causal attributions account for the increased intimacy frequently observed in mediated communication. In the experiment participants were randomly assigned to a face-to-face or computer-mediated interaction with a confederate who made either high-or low-intimacy self-disclosures. Results indicated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
164
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(179 citation statements)
references
References 55 publications
10
164
0
5
Order By: Relevance
“…When initial information is favorable, they tend to extrapolate impressions and affective reactions in a positive way, creating idealized impressions of their online communication partners and their relationships. This theoretical model is supported by empirical studies demonstrating that online communication has a more substantial effect on interpersonal impressions than face-to-face or telephone communication (Carr & Foreman, 2016;Jiang, Bazarova, & Hancock, 2011;Walther, DeAndrea, & Tong, 2010). And specifically related to self-esteem, a study using experienced sampling method demonstrated that text-based communication was more strongly related to self-esteem than face-to-face communication (Gonzales, 2014).…”
Section: Introductionsupporting
confidence: 60%
“…When initial information is favorable, they tend to extrapolate impressions and affective reactions in a positive way, creating idealized impressions of their online communication partners and their relationships. This theoretical model is supported by empirical studies demonstrating that online communication has a more substantial effect on interpersonal impressions than face-to-face or telephone communication (Carr & Foreman, 2016;Jiang, Bazarova, & Hancock, 2011;Walther, DeAndrea, & Tong, 2010). And specifically related to self-esteem, a study using experienced sampling method demonstrated that text-based communication was more strongly related to self-esteem than face-to-face communication (Gonzales, 2014).…”
Section: Introductionsupporting
confidence: 60%
“…Past studies have predominately focused on media richness, which circumscribes the richness of information delivered by the communication medium (e.g., Caplan and Turner 2007, Jiang et al 2010, Ratan et al 2010. Furthermore, extant research suggests that media richness facilitates the development of meaningful online relationships (e.g., Dennis et al 1999, Sheer 2011.…”
Section: Hyperpersonal Framework Andmentioning
confidence: 97%
“…Intimacy and self-disclosure are key concepts in relationship development and build on reciprocity between individuals. TmC, like FtF relationships, is dependent on partner responsiveness (Jiang, Bazarova, and Hancock 2011), but additional time is required to facilitate social over task-oriented interactions. When the media rate is factored in with time online, the contribution to relationship development has greater potential to be realised.…”
Section: Regular Communication and Connectedness For Developing A Senmentioning
confidence: 99%